The relationships between fluoride intake levels and fluorosis of late‐erupting permanent teeth. (29th December 2017) - Bhagavatula, Pradeep; Curtis, Alexandra; Broffitt, Barbara; Weber‐Gasparoni, Karin; Warren, John; Levy, Steven M.
Abstract: Objectives: To examine the relationships between fluoride intake levels and fluorosis of late‐erupting permanent teeth. Methods: The current study used information collected from 437 children in the longitudinal Iowa Fluoride Study. Participants' fluoride intake information was collected using questionnaires from birth to age 10 years. Estimated mean daily fluoride intake was categorized into low, moderate, and high intake tertiles for each age interval (2‐5, 5‐8, and 2‐8 years). Bivariate analyses were performed to study the relationships between self‐reported fluoride intake levels during three age intervals and dental fluorosis. Results: For canines and second molars, the prevalence of mostly mild fluorosis was less than 10% in the lowest fluoride intake tertile and more than 25% in the highest intake tertile. For both first and second premolars, the prevalence in the low and high intake tertiles was approximately 10‐15% and 25‐40%, respectively. When estimated total daily fluoride intake was 0.04 mg/kg BW during ages 2‐8 years, the predicted probability of fluorosis was 16.0%, 20.5%, 21.8%, and 15.4% for canines, 1st and 2nd and premolars and 2nd molars, respectively. We found that an incremental increase in fluoride intake during the age 5‐ to 8‐year interval led to greater odds for development of mostly mild dental fluorosis in late‐erupting teeth compared to increases in fluoride intake during other age intervals. Conclusions: Our results clearly show that dental fluorosis prevalence is closely related to fluoride intake levels and that teeth have greater susceptibility to fluoride intake during certain age intervals.